2009
DOI: 10.1017/s0266462309090060
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the quality of mini-HTA

Abstract: The results show that the quality of the information in many cases is insufficient. There is a strong need for quality assurance of mini-HTAs to improve the accuracy of the information, however, without harming the timeliness and the limited use of resources in producing the reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 10 publications
0
39
0
1
Order By: Relevance
“…This diversity makes evaluating recommendations from rapid reviews challenging as it is unclear what effect the potential biases introduced into the review process might have on the results [65,66]. Additionally, Gannon et al [34] noted that because of the shortened timelines, rapid reviews may be prone to bias.…”
Section: Discussionmentioning
confidence: 99%
“…This diversity makes evaluating recommendations from rapid reviews challenging as it is unclear what effect the potential biases introduced into the review process might have on the results [65,66]. Additionally, Gannon et al [34] noted that because of the shortened timelines, rapid reviews may be prone to bias.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the use of mini-HTA reports in assessing investment decisions at hospital level, Kidholm et al (13) suggested that the data provided by such reports might sometimes be deemed insufficient, especially when information about the selection and interpretation of the clinical literature is missing. If credible advice were to be used in the acquisition of new HTs, we would agree it is necessary to guarantee the quality of mini-HTAs reports.…”
Section: Discussionmentioning
confidence: 99%
“…either more "policy-making" oriented [3] or more locally based, such as Hospital Based HTA or mini HTA from Denmark, although the latter shows some limitations [4], used when the evaluation considers a very localized situation.…”
mentioning
confidence: 99%